2018
DOI: 10.1371/journal.pone.0203786
|View full text |Cite
|
Sign up to set email alerts
|

Biodeterioration of plasma pretreated LDPE sheets by Pleurotus ostreatus

Abstract: Low-density polyethylene (LDPE) waste generates an environmental impact. To achieve the most suitable option for their degradation, it is necessary to implement chemical, physical and biological treatments, as well as combining procedures. Best treatment was prognosticated by Plackett-Burman Experimental Design (PB), evaluating five factors with two levels (0.25 mM or 1.0 gL-1 glucose, 1.0 or 2.0 mM CuSO4, 0.1 or 0.2 mM ABTS [2, 20-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid)], pH 4.5 ± 0.2 or 7.0 ± 0.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(74 citation statements)
references
References 80 publications
3
67
0
Order By: Relevance
“…In studies on the plastics degradation for P. ostreatus, the authors also observed chemical and physical changes similar to the observed in our study [29,30].…”
Section: Scanning Electron Micrograph Of Oxo-biodegradable Plastics Bsupporting
confidence: 89%
See 2 more Smart Citations
“…In studies on the plastics degradation for P. ostreatus, the authors also observed chemical and physical changes similar to the observed in our study [29,30].…”
Section: Scanning Electron Micrograph Of Oxo-biodegradable Plastics Bsupporting
confidence: 89%
“…According to them, this time of exposure is insufficient for other physical or chemical changes, concluding that the mechanical properties alterations, such as the reduction of breaking energy and elasticity facilitated the fungal colonization of plastic waste. The chemical and physical changes in the low-density polyethylene (LDPE) was observed after pretreated of the LDPE sheets with low discharge plasma (O 2 , 3.0 × 10 −2 mbar, 600 V) for 6 minutes [29,30]. According to authors, this pretreated was important by plastics biodeterioration by P. ostreatus.…”
Section: Steps and Technics Used For Monitoring The Abiotic And Biotimentioning
confidence: 99%
See 1 more Smart Citation
“…Plant and flower grower industries produce vast quantities of organic waste (bark, sawdust, leaves, stems, fragmented flowers, among others) containing high amounts of lignin, cellulose and hemicellulose [46]. In addition, these companies use low and high-density polyethylene (LDPE and HDPE) with different purposes: packing planting material, seedling rooting, mulching, greenhouse fabrication and wrapping of product [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…To carry out simultaneous bioconversion of LCB and LDPE oxo different types of microorganisms can be used, by themselves, in co-cultures or in consortiums [1517]. From an array of microorganisms studied, lignolytic white rot fungi are the most efficient to perform partial or total biotransformation of these types of solid residues [1619] because of: ( i ) form networks of mycelia and produce exopolysaccharides that aid in colonization of both materials [6,20], ( ii ) produce an ample gamut of extracellular enzymes such as ligninases (E.C. 1.11.1.14), cellulases (E.C.…”
Section: Introductionmentioning
confidence: 99%